P43-S Different stimuli painful or not may explore diffuse noxious inhibitory control in humans. Issue 7 (July 2019) - Convers, Philippe; Creac'h, Christelle; Peyron, Roland
Abstract : Background: Diffuse noxious inhibitory control (DNIC) can be studied when using different painful stimulations before and after a cold pressor test (CPT). The aim of this study is to affirm a modulation of pain responses when applying CPT in healthy subjects. Methods: 15 normal subjects (9 males, 6 females) were included. They signed informed consent. The stimulus was applied on the dorsum of right hand. The CPT was applied on the left foot for five minutes. The intensity of pain was noted on a visual analogic scale (VAS). Evoked potentials (EP) were recorded. The three different types of stimulation were: heat laser stimulus, electrical stimulus with a circular electrode (elec-pain-4 Walter graphtek), cold stimulus with an air puff. The paradigm was: time 1 stimulation baseline; time 2 repeated stimulation baseline then CPT applied for 5 min; time 3 stimulation 5 mn after CPT; time 4 stimulation 30 mn after CPT. Values of VAS were noted. Latencies and amplitudes of vertex potentials N2/P2 were measured. The different sessions were compared between them (student test) as well for psychophysical and EP data. Results: Whatever the stimulus, VAS and EP in time 1 and time 2 were not different. The responses were diminished five minutes after CPT and could return to baseline or remain diminished after thirty minutes. Conclusion: These paradigms confirm the lack of stimulus specificity able to induce the startup of DNIC. Such techniques may help to study pain control in patients.